Influence of games in the field of artificial intelligence (Revista Brasileira de Contabilidade e Gestão, 2013)
Game development is a field that attracts many developers and has been growing over the years. Parallel to this growth, the use of artificial intelligence techniques embedded in this class of software increases, providing realistic appearance and fun to the games available on the market. In this context, games strongly influence on the development of artificial intelligence techniques, which will be addressed in the course of this work. To elucidate the abovementioned concepts and define the factors of influence, a study was conducted on the techniques of artificial intelligence in electronic games. Aspects regarding the development of intelligent games and the software to help developers in the area were also raised.
Keywords: electronic games; artificial intelligence; Game AI